2015
DOI: 10.4049/jimmunol.1501209
|View full text |Cite
|
Sign up to set email alerts
|

Age-Associated B Cells: A T-bet–Dependent Effector with Roles in Protective and Pathogenic Immunity

Abstract: A newly discovered B cell subset, Age Associated B Cells, expresses the transcription factor T-bet, has a unique surface phenotype, and progressively accumulates with age. Moreover, B cells with these general features are associated with viral infections and autoimmunity in both mice and humans. Here we review current understanding of the characteristics, origins, and functions of these cells. We also suggest that the protective versus pathogenic actions of these cells reflect appropriate versus aberrant engag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
202
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(224 citation statements)
references
References 53 publications
18
202
0
1
Order By: Relevance
“…Together these data strongly suggest that T-bet-dependent activation of autoreactive B cells takes place during the development and/ or progression of human autoimmunity. Moreover, several studies have indicated that human CD21 -CD19 hi B cells (the phenotype associated with T-bet expression) are enriched in autoreactivity, supporting the idea that T-bet-expressing B cells are key mediators of human autoimmunity (9,44 7,9,18). Overall, we can conclude that human T-bet + B cells very closely recapitulate their mouse counterparts, suggesting their overall similar function in the development of autoimmunity.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Together these data strongly suggest that T-bet-dependent activation of autoreactive B cells takes place during the development and/ or progression of human autoimmunity. Moreover, several studies have indicated that human CD21 -CD19 hi B cells (the phenotype associated with T-bet expression) are enriched in autoreactivity, supporting the idea that T-bet-expressing B cells are key mediators of human autoimmunity (9,44 7,9,18). Overall, we can conclude that human T-bet + B cells very closely recapitulate their mouse counterparts, suggesting their overall similar function in the development of autoimmunity.…”
Section: Discussionsupporting
confidence: 76%
“…In agreement with our findings, a recent study by Becker et al demonstrated elevated levels of T-bet expression in B cells obtained from peripheral blood mononuclear cells of SLE patients when compared with healthy donors, suggesting that T-bet expression in B cells may be critical for the development of lupus in humans (15). Others have reported that T-bet-expressing B cells are associated with Crohn's disease activity (16), and an increased expression of T-bet in B cells was found in a patient with MS and celiac disease (17), altogether suggesting an important role for T-bet-expressing B cells in human autoimmunity (18).…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by our observations that addition of anti-CD40 with the IL-21 and IFN-γ cytokines engenders survival and induces T-bet expression and class-switching to IgG 2a/c . Since T-bet + B cells have been reported in the context of aging, autoimmunity, and infections (74), these cells may arise in response to TLR9 ligands delivered via the BCR, and while such signals would ordinarily trigger apoptosis, cognate T cell help and additional cytokines could result in the breakthrough of autoantibody production. Additionally, in vivo and in vitro data suggest that RNA-sensing receptors, such as TLR7, do not promote post-proliferative cell death, but instead foster plasma cell differentiation (75).…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear whether the TLR agonists act directly on the ABC or through an indirect mechanism or both. In Cancro’s in vitro study TLR agonist stimulation was required for in vitro proliferation of ABC from unimmunized mice [13] and more recent studies by Rubtsov and Marrack that indicate the generation of ABC is dependent on TLR agonists in their autoimmune models [14,20]. …”
Section: Role Of Tlr Stimulation In the Generation Of Ab-secreting Abcmentioning
confidence: 99%